Effect of Substitution of Bovine Rumen Epithelial Tissue Scrapings for Fishmeal on the Growth Performance, Nutrient Utilization and Carcass Characteristics of Broiler Chickens - Salami, SA; Ali, A; Babatunde, OT (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Abstract. An eight-week feeding trial was conducted to evaluate the performance, nutrient utilization and carcass characteristics of broiler chickens fed varied levels of bovine rumen epithelial tissue scrapings (BRETS) in replacement for fish meal at 0, 50 and 100% levels of substitution. Fifty four birds were used for the study and the birds were randomly distributed into three (3) dietary treatments which were randomly assigned to the rations. Feed and water were supplied ad libitum and data were collected on the feed intake, weight gain, feed conversion ratio and nutrient utilization. Data were also collected on the carcass characteristics after some birds had been slaughtered at the end of the experiment. Data collected were subjected to one-way analysis of variance and significant differences were indicated using Duncan multiple range test to separate the means. Results indicated that there was significant difference (P<0.05) in the feed intake, feed conversion ratio, nutrient utilization and cut-up parts, except for the lung and heart. However, there was no significant difference (P>0.05) in the weight gain, heart and lung weights. It was concluded that up to 50% BRETS inclusion as substitute for fish meal protein could be employed without any adverse effect, to maintain the quality of the broiler chicken while minimizing the high cost of whole fishmeal since BRETS is an abattoir by-product that is readily available locally. Keywords: Broiler chicken, epithelial tissue scrapings, fish meal, bovine rumen. Abstrak. Sebuah percobaan pakan selama delapan minggu dilakukan untuk mengevaluasi kinerja, pemanfaatan nutrisi dan karakteristik karkas ayam broiler yang diberi berbagai tingkat kerokan jaringan epitel (BRETS) rumen sapi sebagai pengganti tepung ikan pada 0 , 50 dan 100% tingkat substitusi. Lima puluh empat ayam broiler yang digunakan untuk penelitian dibagi secara acak ke dalam tiga (3) perlakuan pakan. Pakan dan air minum diberikan secara tak terbatas dan dicatat data konsumsi pakan, pertambahan bobot badan, rasio konversi pakan dan pemanfaatan nutrisi. Data lainnya yang diamati adalah karakteristik karkas setelah ayam dipotong pada akhir percobaan. Data yang dikumpulkan dianalisis dengan analisis ragam satu arah dan perbedaan nyata ditunjukkan dengan uji jarak berganda Duncan untuk memisahkan nilai tengah. Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan (P<0,05) pada konsumsi pakan, rasio konversi pakan, pemanfaatan nutrisi dan bagian-bagian potongan ayam, kecuali paru-paru dan jantung. Namun demikian, tidak ada perbedaan yang signifikan (P>0,05) pada bobot badan, jantung dan bobot paru-paru. Disimpulkan bahwa pemberian BRETS hingga 50 % sebagai pengganti protein tepung ikan dapat digunakan tanpa efek samping, untuk menjaga kualitas ayam broiler sambil menekan biaya tepung ikan yang mahal karena BRETS adalah hasil samping rumah pemotongan hewan yang tersedia secara lokal. Kata kunci: Ayam broiler, kerokan jaringan epitel rumen sapi, tepung ikan,SA Salami et al./Animal Production 15(1):15-23, January 2013